2008
DOI: 10.1007/s10549-008-9992-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thrombospondin-1 on breast cancer metastasis

Abstract: Thrombospondin-1 (TSP-1) has been proposed to have both pro-metastatic and anti-metastatic properties. To elucidate its role in breast cancer metastasis, we compared tumor progression in the polyomavirus middle T antigen (Pyt) transgenic mouse and the TSP-1-null Pyt transgenic mouse. We characterized the tumors in these mice at 45, 60 and 90 days of age. Tumor size, areas of necrosis, macrophage infiltration, levels of active and total TGF-β, vessel morphology, and lung and blood metastasis were measured in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
87
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 57 publications
10
87
0
1
Order By: Relevance
“…Hence, in the absence of Tsp-1 production in the lung, Psap failed to suppress metastasis formation by LLC cells. The observed lower numbers of metastases in the Tsp-1 KO mice compared with their wild-type counterparts is consistent with previously reported findings (22) and could be explained by a compensatory 4.5-fold increase in Tsp-2 production induced by LLC cells in these mice, a phenomenon not observed in wild-type mice or human tumors (Figs. S5 and S6).…”
Section: Tsp-1 Expression Is Required For Prosaposin-mediated Suppressupporting
confidence: 92%
“…Hence, in the absence of Tsp-1 production in the lung, Psap failed to suppress metastasis formation by LLC cells. The observed lower numbers of metastases in the Tsp-1 KO mice compared with their wild-type counterparts is consistent with previously reported findings (22) and could be explained by a compensatory 4.5-fold increase in Tsp-2 production induced by LLC cells in these mice, a phenomenon not observed in wild-type mice or human tumors (Figs. S5 and S6).…”
Section: Tsp-1 Expression Is Required For Prosaposin-mediated Suppressupporting
confidence: 92%
“…A number of studies have previously shown that TSP-1 is a mitogeninducible immediate-early response gene (18) and is intimately involved in the regulation of cellular proliferation through effects on integrin pathways (19). Furthermore, consistent with our results, TSP-1 has been shown to be involved in the integrin pathways that can affect tumor cell adhesion (20) or migration/invasion (9).…”
Section: Discussionsupporting
confidence: 89%
“…To determine whether B-Raf V600E could affect ECM composition and drive thyroid cancer progression, we validated various genes linked to invasion and metastasis and focused our in vitro and in vivo validations on TSP-1. TSP-1 and its target TGF-β1 are crucial regulators of epithelial cell growth, motility, polarity, and morphogenesis (9,10) and are important in stromal/epithelial interaction and angiogenesis. Whereas the role of TSP-1 as an inhibitor of tumor angiogenesis is well documented, its biological action in tumor progression and metastasis requires further study (9,10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations